PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KEPUASAN KERJA PEGAWAI BALAI PENGELOLA KERETA API RINGAN SUMATERA SELATAN - Anjel, Anjel; Maliah, Maliah; Usman, Benny (Universitas Nusa Cendana, 2024)
This study aims to determine the effect of compensation and motivation on employee job satisfaction. The method used in this study is a quantitative method with the number of samples studied were 41 respondents. The data analysis techniques used in this study are multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, t-test, and F-test using the SPSS 26 program. The results of the study can be concluded that partially and simultaneously there is a significant influence between compensation and motivation variables on work satisfaction at the Riangan Railway Management Center of South Sumatra. Keywords: Compelnsation; Motivation; Job Satisfaction